Radiological Patterns Integration with Duration of Illness in COVID-19 Pneumonia as ‘Evolved’ and ‘Evolving’ Radiological Phenotypes: A Single Center Experience (Journal of Medicine, 2023)
Background: Radiological phenotypes are radiological patterns or observable characteristics of COVID- 19 pneumonia.Methods: Prospective observational study, included 3000 COVID-19 RT-PCR confirmed cases with lung involvement documented and categorized on HRCT thorax at entry point as mild, moderate and severe as per lung segment involvement bilaterally and follow up CT thorax imaging at six months post discharge from hospital. Radiological phenotypes were categorized as ‘Evolved’ and ‘Evolving’ as per radiological features and analysed with inflammatory markers and interventions required in indoor setting including ventilatory support. Age, gender, Comorbidity, laboratory parameters and use of BIPAP/NIV in COVID-19 cases and outcome as with or without lung fibrosis were key observations. Statistical analysis is done by using Chi square test.Results: In study of 3000 COVID-19 RT PCR confirmed pneumonia, ‘Evolved’ and ‘Evolving’ radiological phenotype patterns were observed in 36.66% and 63.33% respectively. Duration of illness, laboratory parameters at entry point (CRP, IL-6, ferritin, LDH, D-dimer) & interventions required in indoor unit has significant association with Radiological phenotypes [p